2018
DOI: 10.3390/ijms19020484
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Omega-3 Polyunsaturated Fatty Acid Supplementation Protects Against Adriamycin and Cyclophosphamide Chemotherapy-Induced Bone Marrow Damage in Female Rats

Abstract: Although bone marrow and bone toxicities have been reported in breast cancer survivors, preventative strategies are yet to be developed. Clinical studies suggest consumption of long chain omega-3 polyunsaturated fatty acids (LCn3PUFA) can attenuate age-related bone loss, and recent animal studies also revealed benefits of LCn3PUFA in alleviating bone marrow and bone toxicities associated with methotrexate chemotherapy. Using a female rat model for one of the most commonly used anthracycline-containing breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Metaphyseal bone sections of MTX and FO-treated group showed marked improvement in the histological architecture of primary and secondary spongiosa trabeculae with BM cavities occupied mostly by developing hemopoietic stem cells. These findings were in agreement with [24] who reported that daily omega-3 PUFAs supplementation during MTX chemotherapy could enhance osteogenic differentiation through induction of osteogenesis factors and also inhibiting expression of osteoclastogenesis as well as adipogenesis factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Metaphyseal bone sections of MTX and FO-treated group showed marked improvement in the histological architecture of primary and secondary spongiosa trabeculae with BM cavities occupied mostly by developing hemopoietic stem cells. These findings were in agreement with [24] who reported that daily omega-3 PUFAs supplementation during MTX chemotherapy could enhance osteogenic differentiation through induction of osteogenesis factors and also inhibiting expression of osteoclastogenesis as well as adipogenesis factors.…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy to mention that, BM adipocytes do not just simply fill the marrow spaces, but can act as negative regulators of the BM microenvironment and have direct functions on hematopoietic cells [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovariectomized mice, supplementation with omega‐3 PUFAs increased femoral neck BMD and decreased osteoclast number . Furthermore, a diet supplemented with fish oil or omega‐3 PUFAs prevented bone loss during chemotherapy, reduced bone resorption markers, and increased bone density in periodontitis . Additionally, a maternal diet rich in omega‐3 PUFAs was correlated with a downregulation of osteoclastogenesis in offspring (Fig.…”
Section: Osteoclasts and Fatty Acidsmentioning
confidence: 86%
“…In this context, doxorubicin, an anthracycline, and cyclophosphamide, an alkylating agent, are often combined and adopted in different protocols. Although effective, especially in advanced tumors, the side effects of this combination on the bone marrow are commonly reported, impairing the hematopoietic function of patients undergoing chemotherapy 3,4 .…”
Section: Introductionmentioning
confidence: 99%